Rhetoric of food authenticity and national identity in the new media - Jamaluddin Aziz; Fuzirah Hashim (Penerbit Universiti Kebangsaan Malaysia, 2021)
The global discourse on food often pivots around the issue of food security. With the new media, the discourse of food as a signifier of a national identity is constantly renewed and contested. This constant renewal and perpetual debate about food authenticity as the nexus of national identity from the Cultural Studies perspective is both the significance and the problem that the present study acknowledges and addresses. The aim of this paper is to identify, analyze and interpret the rhetorical strategies used by the media audience to reveal their attitude towards the issue. Using convenience sampling technique, a set of discourse samples is selected from the comment sections of articles on food authenticity across the new media. The corpus is analyzed using key concepts or canons in rhetoric, which are Logos, Ethos and Pathos. In addition, three rhetorical canons, invention, arrangement and style, are also used as units of analysis. The study finds that rhetors did not use the Logos (logic and fact) as one of their strategies to persuade readers to be on their side. Instead, they appealed to ethos (character and credibility) and Pathos (emotion). This evinces the idea that the media audience writing in a comment section in the new media are not basing their writing on the need to appeal to logic and fact (Logos), or proactively, but instead they are more reactionary (personal and emotive). This finding contributes towards the understanding of the media audience’s rhetorical strategies in the new media.